ONLINE STUDENT ORAL CASE ANALYSIS DURING COVID-19 PANDEMIC: A CASE STUDY - endin nokik stujanna; Gea Pandhita; Rizka Aries Putranti; Bety Semara Lakshmi; Wawang Setiawan Sukarya (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Currently, medical education program has implemented the student-centred education method by using Problem Based Learning (PBL) paradigm. One of its assessment methods is Student Oral Case Analysis (SOCA). This method determines the rhetorical and linguistic characteristics of students by using specific communication methods. An offline assessment is temporarily selected for the SOCA. Due to the pandemic, strict health protocols for medical education should be followed by any parties. As a result, there is a modification for learning method when offline (face-to-face) activities should be shifted to online activities, includes SOCA assessment. However, to meet the objective of the learning, the modification needs careful planning and implementation. This study aimed to describe about how The Faculty of Medicine, Prof. DR. Hamka Muhammadiyah University (UHAMKA) successfully carried out SOCA assessment for their students through online method.Case Discussion: During the outbreak of Covid-19 The Faculty of Medicine, UHAMKA, has changed SOCA assessment from offline mode to online mode by using Zoom application. Pre-exam preparation includes a review of the questions by the Medical Education Unit team, preparation of human resources (examiners, supervisors), and supporting applications. The assessment is conducted by applying some adjustments between medical learning activities and current health protocols. Subsequently, upon completion of the assessment, an evaluation is conducted using a questionnaire and random interview technique.Conclusion: The Zoom platform’s online method is an effective option for SOCA assessment during the pandemic. It can be concluded that the exam was successfully implemented to the student and it produced relatively similar results with an offline exam. The online SOCA assessment at Faculty of Medicine UHAMKA was well organized without any serious problem.